Home hospice care in Nepal: a low-cost service in a low-income country through collaboration between non-profit organisations - Binay K Shah, MD; Tara Shah, BSN (Elsevier, 2017)
Background: Nepal is a low-income country in south Asia with a population of more than 27 million people. Because of late diagnosis and poor access to care, almost 90% of approximately 60 000 people diagnosed with cancer in Nepal annually will die within 1 year of diagnosis. Here, we describe our experience in successfully establishing a home hospice programme in Kathmandu, Nepal. Methods: In 2015, Binaytara Foundation, a US-based non-profit organisation, collaborated with a Nepal-based non-profit organisation, Cancer Care Nepal, to develop a home hospice programme in Kathmandu. We interviewed 150 terminally ill patients and their family to investigate the need for a hospice programme. A project leader (a Nepali physician) was appointed. In the second phase of the programme, we trained health-care providers and implemented electronic medical records. A hospice nurse practitioner from Idaho, USA, travelled to Nepal to train 15 Nepali nurses. A motorbike was provided for the hospice nurse to travel to patients' homes. Findings: The hospice programme was launched in January, 2016. By September, 2016, 65 patients had been enrolled in home hospice care. The service is provided free of charge to the patients and their family. The cost of running the hospice programme is US$17 per day. All costs, including equipment, salary, staff training, electronic medical records, fuel, and other monthly expenses have been paid for by Binaytara Foundation. Interpretation: Home hospice programmes are very important in low-income countries like Nepal where most patients with cancer are diagnosed at late stages, and many patients do not have access to cancer centres. To make a home hospice project successful, several factors, such as the selection of an appropriate local partner organisation, training, and financial support are necessary and the project should respect local cultural contexts. Funding: None